PENGUATAN KARAKTER RELIGIUS PESERTA DIDIK MELALUI PROFIL PELAJAR PANCASILA DI KAWASAN INDUSTRI - Nabila, Salsa; Amrullah, Muhlasin (Inteligensi : Jurnal Ilmu Pendidikan, 2024)
The implementation of this research was carried out with the aim of in-depth assessment regarding the strengthening of religious character possessed by students through the Pancasila Student Profile approach in elementary schools in the Industrial Estate area. In this study, the sample taken was SDN Sedati Agung Sidoarjo. A descriptive qualitative approach was chosen in conducting this research, with a case study method. The data obtained were collected through observation activities during the research, interviews with research subjects, and documentation activities. The research subjects were the principal, class teachers, and students at the school. Furthermore, the data obtained was analysed through the process of collecting data, reducing data, presenting data, and drawing conclusions. The results of the research obtained the fact that the application of strengthening religious character at SDN Sedati Agung also implements it through strengthening the student profile of Pancasila, as well as all routine activities that are continuous with the vision and mission at SDN Sedati Agung Sidoarjo. This is applied in the school environment so that students can easily form a religious character under the direction and guidance of the teacher, along with the values embedded in Pancasila. The achievement of activities at SDN Sedati Agung has been well implemented and has become a routine activity for all students.